(untitled) (Global Journal of Human-Social Science, 2023)
This paper addresses recourse to quotations as a polyphonic resource conveying a particular ideology We argue that they serve to persuade audiences by eliciting an emotional response pathos that affects the transmission of ethos both of the locutor Maingueneau 2002b and the community it claims to represent By examining the quotes found on the President s official Twitter account and in his public speeches we aim to identify the emotions that are semiotized by citations or secondary aphorizations Maingueneau 2012 We later examine their intended persuasive impact on the target audience In short we conclude that aphorizations play a crucial role in the ideological construction of discourse in the political sphere